2016
DOI: 10.1007/s10943-016-0343-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Family Structure on Religion and Spirituality of Emerging Adult Males and Females

Abstract: This study examined measures of religion and spirituality in a sample of male and female emerging adult college students whose parents were either divorced or intact using the Personal Religious Inventory, the Duke University Religion Index, the Daily Spiritual Experiences Scale, the Spiritual Transcendence Scale, and the Spiritual Involvement and Beliefs Scale. Data were collected online, and 66% of participants received extra credit for participating. A main effect of sex was found, as females reported signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In the current study, female older adults had higher levels of religious coping than male older adults. This finding is consistent with previous studies, in which female seniors reported higher levels of religiousness than did male seniors (Garg Chauhan and Sabreen 2018;Handal and Lace 2017;Henrie and Patrick 2014). This finding is also consistent with terror management theory (TMT), which states that being male is positively associated with religious doubt and negatively associated with religiousness (Henrie and Patrick 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, female older adults had higher levels of religious coping than male older adults. This finding is consistent with previous studies, in which female seniors reported higher levels of religiousness than did male seniors (Garg Chauhan and Sabreen 2018;Handal and Lace 2017;Henrie and Patrick 2014). This finding is also consistent with terror management theory (TMT), which states that being male is positively associated with religious doubt and negatively associated with religiousness (Henrie and Patrick 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Recent work has extended this investigation to spirituality in emerging adulthood, a period in which spirituality is often explored (Creech et al 2013;Handal and Lace 2017;Piedmont et al 2009). Additionally, emerging adults, those between the ages of 18 to 25 (Arnett 2000), may be at an increased risk for first onset of mental health problems (Kessler et al 2005;Zivin et al 2009).…”
mentioning
confidence: 99%
“…Respondents were aged from 23 to 59 and all were female. This was deemed acceptable as males may react differently to spiritual content as they tend to be less spiritual and religious than females (Flere, 2007; Handal and Lace, 2017; Miller and Hoffman, 1995). Furthermore, in 2021, females out number males as users of Facebook in most western contexts including the USA, UK and Australia (Statista, 2021).…”
Section: Methodsmentioning
confidence: 99%